2010
DOI: 10.1007/s13187-010-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

The Art and Science of Cancer Education and Evaluation: Toward Facilitating Improved Patient Outcomes

Abstract: Cancer education is a constantly evolving field, as science continues to advance both our understanding of cancer and its effects on patients, families, and communities. Moving discoveries to practice expeditiously is paramount to impacting cancer outcomes. The continuing education of cancer care professionals throughout their practice life is vital to facilitating the adoption of therapeutic innovations. Meanwhile, more general educational programs serve to keep cancer patients, their families, and the public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[10] This effectiveness has increased with the use of versatile methodologies and interactive techniques. [11] Most importantly, the interventions with community participation have proved more effective. [1213] Moreover, recipients’ preferences of information and participation which differ according to time, setting, as well as their characteristics must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…[10] This effectiveness has increased with the use of versatile methodologies and interactive techniques. [11] Most importantly, the interventions with community participation have proved more effective. [1213] Moreover, recipients’ preferences of information and participation which differ according to time, setting, as well as their characteristics must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…Substantive work determining the efficacy of varying teaching styles in different medical disciplines suggests that multiple educational methodologies implemented together with interactive techniques are most effective particularly when combined with repeated exposures. [19][20] It is further recognized that students vary in their learning styles and thus a ''one-size-fits-all'' model is difficult to achieve. 21 There are strengths and weaknesses to this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, providing evidence-based education to patients has become recognized as standard of care. Research has shown that most effective educational methods include patient decision aids, counseling, videos, computer-based information or education, and interactive computer and multimedia interventions (Johnson et al, 2011).…”
Section: Nursing Implicationsmentioning
confidence: 99%